INNOVATIVE APPROACHES TO INCREASING THE COMPETITIVENESS OF WALNUT PRODUCTION - STADNIK, MYKOLA; LUTS, PAVLO; RUTKEVYCH, VOLODYMYR; PUSHKA, OLEXANDR (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article considers innovative approaches to increasing the competitiveness of walnut products by improving the technology of post-harvest processing using tunnel dryers. The influence of drying modes (preheating at 28–35 °C, main drying at a temperature of 35–45 °C with controlled air humidity and final adjustment to equilibrium humidity with subsequent cooling) on the quality of walnut kernels is analyzed. It was established that controlled moisture removal ensures the preservation of the structural integrity of the kernel, reduces the risk of shell cracking and darkening, contributes to the preservation of taste properties and increases the market value of the product. The introduction of automated process control systems and the integration of heat recovery and air dehumidification increases energy efficiency and reduces processing time, making the technology economically feasible for industrial application. Additional use of ozonation after drying is an effective sterilization method that prevents the development of mold fungi and other microorganisms, thereby extending the period of safe storage. The additional use of ozonation or ultraviolet irradiation after drying provides effective sterilization, prevents the development of mold fungi and other microorganisms and extends the safe storage period of products. The proposed technology takes into account the physicochemical characteristics of Ukrainian nuts, drying modes and mass transfer, which allows reducing production losses and increasing the country's export potential. The use of modern drying complexes with heat recovery systems, automated control of process parameters and the introduction of environmentally friendly disinfection technologies ensures high quality and stability of the finished product. The results obtained can become the basis for the formation of effective production strategies aimed at strengthening the positions of Ukrainian walnut producers in the global competitive environment.
Keywords: walnuts; humidity; drying agent; drying chamber; coolant speed; temperature; fan; energy efficiency